Tren Hijrah Muslim Perkotaan di Media Sosial: Konstruksi, Representrasi dan Ragam Ekspresi - Taufiq, Thiyas Tono; Royanulloh, Royanulloh; Komari, Komari (FIKRAH, 2022)
Millennial urban Muslims represent the trend of hijrah in Indonesia. Given that the urban millennial community has adequate Internet access. In addition, hijrah for them is not only present as a spiritual phenomenon but has also become a trend and lifestyle. Hijrah has become a more aggressive phenomenon in urban areas than in rural areas. This article will describe hijrah society, not only in real daily social life but also through social media on the Instagram platform with the hashtag hijrah (#hijrah). This study uses a qualitative method with a virtual ethnographic approach and uses social media space. The trend of hijrah that is displayed contains many meanings and various expressions. First, hijrah is a persuasive tool to make accounts more popular and business, spreading social-religious values. Second, hijrah is the meaning of self-existence. Urban Muslims use social media as a tool to express their religious identity through content with the hashtag hijrah (#hijrah). Third, as a form of self-change. In religious education, in dress, behavior, attitude, and embodiment of a harmonious family. Fourth, hijrah represents the proliferation of Islamic groups and movements, especially the Salafi community and some students (santri)